Fifth Review of the Fund's Data Standards Initiatives. (Policy Papers; Policy Paper ;, 2003)
This paper reviews developments under the Fund's Data Standards Initiativ--the Special Data Dissemination Standard (SDDS) and the General Data Dissemination System (GDDS)--and their integration under the Data Quality Program. The paper discusses proposals for updating the SDDS and the GDDS to maintain their relevance and reflect evolving international best practice, and for follow-up on the data module of the Report on the Observance of Standards and Codes (ROSC). The paper also proposes the development of a Compendium on Good Statistical Practices.